POSSENTI, Sírio (2010). Humor, língua e discurso (Revista Latinoamericana de Estudios del Discurso, 2020)
POSSENTI, Sírio (2010). Humor, língua e discurso. São Paulo: Contexto. 183 pp. ISBN: 978-85-7244-480-4.